2015
DOI: 10.1159/000369977
|View full text |Cite
|
Sign up to set email alerts
|

Novel Antitussive Effect of Suplatast Tosilate in Guinea Pigs

Abstract: We studied the antitussive effects of suplatast, a Th2 cytokine inhibitor, and compared them with the effects of codeine using an experimental cough model in guinea pigs. Suplatast and codeine dose-dependently inhibited cough caused by mechanical stimulation of the larynx, but they did not inhibit cough caused by mechanical stimulation of the bifurcation of the trachea. In guinea pigs with bronchitis, suplatast had an antitussive effect on cough caused by stimulation of the larynx, whereas codeine did not inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In addition, we have reported that a cough induced by the mechanical stimulation of tracheal bifurcation is resistant to treatment by codeine (41). Our own preliminary study showed that suplatast inhibits this codeine-resistant cough (49). Interestingly, ophiopogonin-D, an active component of Bakumondo-to, which is a Chinese herbal medicine and is effective for intractable coughs, also inhibits the excitability of paratracheal ganglia neurons, although inhibition mechanisms are different between the two substances.…”
Section: L776mentioning
confidence: 96%
“…In addition, we have reported that a cough induced by the mechanical stimulation of tracheal bifurcation is resistant to treatment by codeine (41). Our own preliminary study showed that suplatast inhibits this codeine-resistant cough (49). Interestingly, ophiopogonin-D, an active component of Bakumondo-to, which is a Chinese herbal medicine and is effective for intractable coughs, also inhibits the excitability of paratracheal ganglia neurons, although inhibition mechanisms are different between the two substances.…”
Section: L776mentioning
confidence: 96%
“…But the codeine-resistant cough was reduced by H 1 antagonists (our unpublished data). Interestingly, suplatast also inhibits this codeine-resistant cough [11]. Therefore, suplatast might be also effective for treating atopic cough.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we found that suplatast inhibits codeine-resistant coughs in guinea pigs with bronchitis or treated with an angiotensin-converting enzyme inhibitor [11]. However, the antitussive effect of suplatast does not appear to be due to the anti-allergic effect caused by Th2 cytokine inhibition.…”
Section: Introductionmentioning
confidence: 98%